PEMBELAJARAN MODEL PjBL DENGAN MEDIA CERITA RAKYAT PAPUA SELATAN DALAM MENINGKATKAN KETERAMPILAN MENULIS NARASI PESERTA DIDIK SEKOLAH DASAR - Welas Riyanti; Aleda Mawene; Triwiyono Triwiyono (Journal of Education Papua Baru, 2025)
Abstract: Elementary school students' narrative writing skills remain a serious concern because many learners still have limited vocabulary, difficulty organizing ideas, and low motivation to write coherent stories. This article synthesizes the conceptual foundation for implementing Project-Based Learning (PjBL) with South Papuan folktales as contextual learning media to strengthen narrative writing skills in elementary schools. Using a literature review approach, this paper examines theories of PjBL, narrative writing, local wisdom-based media, and relevant previous studies on writing instruction. The synthesis shows that PjBL can guide students through questioning, project planning, investigation, drafting, revision, presentation, and reflection, while South Papuan folktales provide culturally close story material that stimulates imagination, moral reasoning, and cultural identity. The proposed learning design positions folktales not merely as reading texts but as sources for story mapping, collaborative discussion, narrative reconstruction, and authentic written products. This conceptual model is expected to support teachers in designing meaningful writing instruction that improves language competence, creativity, critical thinking, and appreciation of local culture. Keywords: Project-Based Learning; South Papuan Folktales; Narrative Writing; Local Wisdom and Elementary School.   Abstrak: Keterampilan menulis narasi peserta didik sekolah dasar masih menjadi persoalan karena banyak peserta didik memiliki kosakata terbatas, kesulitan mengorganisasi gagasan, dan motivasi rendah dalam menyusun cerita yang runtut. Artikel ini mensintesis landasan konseptual penerapan model Project-Based Learning (PjBL) dengan media cerita rakyat Papua Selatan sebagai media pembelajaran kontekstual untuk memperkuat keterampilan menulis narasi di sekolah dasar. Melalui pendekatan kajian pustaka, artikel ini menelaah teori PjBL, keterampilan menulis narasi, media berbasis kearifan lokal, serta hasil penelitian terdahulu yang relevan dengan pembelajaran menulis. Hasil sintesis menunjukkan bahwa PjBL dapat membimbing peserta didik melalui pertanyaan pemantik, perencanaan proyek, investigasi, penyusunan draf, revisi, presentasi, dan refleksi, sedangkan cerita rakyat Papua Selatan menyediakan bahan cerita yang dekat dengan budaya peserta didik, merangsang imajinasi, penalaran moral, dan identitas budaya. Model konseptual ini menempatkan cerita rakyat tidak sekadar sebagai teks bacaan, tetapi sebagai sumber pemetaan cerita, diskusi kolaboratif, rekonstruksi narasi, dan produk tulisan autentik. Kata kunci: Project-Based Learning; Cerita Rakyat Papua Selatan; Menulis Narasi; Kearifan Lokal dan Sekolah Dasar